Osteochondral lesion of the talus in a collegiate basketball player: a case report - Atwood, M. A. (International Journal of Athletic Therapy & Training, 2015)
Key points: Osteochondral lesions of the talus should be suspected in patients with persistent pain or discomfort following conservative ankle treatment. Magnetic resonance imaging should be used to identify osteochondral lesion(s) in the ankle. Hip and knee dysfunction need to be assessed following ankle injury